Investigasi Faktor Kunci Penentu Keterlibatan Istri Petani dalam Kegiatan Usahatani - Winarti, Lili; Andriyati, Yuli; Permadi, Rokhman; Saifullah, M. Akbar; Soddiki, Ahmad (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The issue of gender equality remains a serious concern in several developing countries, including Indonesia. On the other hand, women, particularly farmer wives, are recognized to have the potential to enhance the welfare of farming families. Therefore, effective solutions need to be formulated to address the issue of the involvement of farmer wives in agriculture, considering the comprehensive factors causing their engagement from various aspects. The main objectives of this research are: 1) To analyze the involvement of farmer wives in pineapple farming. 2) To analyze the determining factors of the involvement of farmer wives in pineapple farming. Purposive sampling was chosen to select the Baamang Hulu Village, Tanah Mas Village, and Tinduk Village in the Baamang Sub-district of East Kotawaringin Regency, Central Kalimantan, as the research locations, with 200 respondents determined using the Snowball sampling method. Sociodemographic characteristics and the level of involvement of farmer wives were analyzed using descriptive analysis, while the determining factors of farmer wives' involvement were analyzed using ordinal logistic regression. The research results indicate that most farmer wives are categorized as having a high level of involvement, with the determining factors influencing their engagement being experience, education, and participation in agricultural associations. This research recommends that to enhance the involvement of farmer wives in agricultural activities, it is necessary to ensure that they have fair and equal access to the resources required to participate in agriculture actively. This includes access to land, water, agricultural technology, financing, and markets. It is also essential to encourage the development of more agricultural associations that accommodate the participation of farmer wives.